Pelaksanaan Inovasi One For Eleven di Kota Solok - Cindy Norhaliza; Mayarni Mayarni (Lembaga Pengembangan Kinerja Dosen, 2023)
Public service is one of the main roles of the government to meet the needs of its people. The implementation of public services will also adapt according to the needs of the community and develop in line with changes in social life. This makes the government always try to foster motivation in creating effective and efficient services so as to provide convenience for the public. The purpose or research of this is to find out and explain how the implementation of One For Eleven Innovation in Solok City and to know and analyze the inhibiting factors that influence the implementation of One For Eleven innovation seen from product innovation, process innovation, research method innovation, strategy or policy innovation and system innovation . This study uses a qualitative method with a descriptive approach. The results of the One For Eleven innovation research in Solok City based on indicators of innovation are included in an innovation. This innovation is included in product innovation because there is a renewal of service media, including in process innovation where there are differences in service flow. This innovation is also included in the innovation of service methods where changes in service delivery. This innovation includes strategy or policy innovation because it has a vision, mission and goal of forming an innovation from the existing reality. In addition, this innovation is also included in system innovation, namely the existence of novelty in the interaction of implementing actors in managing innovation, but the implementation of innovation and its utilization by the community is not optimal because there are still many prospective brides who do not know about this innovation. The lack of socialization of innovation by implementers to the community so that there are still many people who do not know about this innovation. Then the difference in the domicile of the bride and groom as a requirement in obtaining this innovation has caused not all bride and groom to receive the One For Eleven innovation service. Lack of coordination between implementing agencies causes executors not to understand their duties.